Secrets and Democracy From Arcana Imperii to WikiLeaks - Quill, Lawrence; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Secrets and Democracy develops a new approach to understanding the centrality of secrecy to political life. From the ancient world to the modern, this book considers the growing importance of secrets, the dilemmas this poses to conceptions of democracy and the challenges that collecting secrets poses to publicity and privacy in the network society.
Keywords: Political science; Political theory; Democracy; International relations; Political philosophy; Political sociology; Political Science and International Relations; Democracy; Political Theory; Political Philosophy; Political Sociology; International Relations; Political Science